Land Use and Land Covers Change Detection of Mareka District (1995 up to 2015) of Dawuro Zone, Southern Ethiopia - Getahun, Shanko Mamo (International Journal of Scientific Research in Civil Engineering, 2018)
Land use and land cover (LULC) change is one of the challenges which strongly influence the process of agricultural development in the study area. Change in land use can negatively affect the potential use of an area and ultimately lead to soil and vegetation degradation that have an impact for loss of agricultural productivity. Land use land cover change analysis was conducted in Mareka district, Southwest Ethiopia between 1995 to 2015. In this study to detect the change image was taken from two different years as reference 1995 and 2015. The land cover change detection was done by using remote sensing and Arc GIS technology. As the result of analysis indicated, the vegetation or forest cover of the Mareka district was minimized from year to year about 33.85 Km2 and due to increment of cultivation practice. Therefore, it is good to strongly introduce modern farming system that allows farmers to get more agricultural products from small farming land plot in study district.
Keywords: Change detection; GIS technology; Land use land cover; Mareka district